Patterns of Community Organizing in the Philippines: A Critique - Nasol, Caridad (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Review of the book Pag-oorganiza ng Pamayanan: Tungo sa Kaunlarang Mula sa Pilipino Para sa Pilipino (Community Organizing: Toward a Development for Filipinos by Filipinos) by Angelito G. Manalili.